PEMILIHAN GUBERNUR LAMPUNG TAHUN 2018 DALAM UPAYA MEWUJUDKAN PEMILIHAN YANG DEMOKRATIS - Wahid, Ali Abdul; Qohar, Abd. (Universitas Islam Negeri Raden Intan Lampung, 2020)
One of the functions of the Election Oversight Body (Bawaslu) is to supervise stages and prevent election violations. The authority of the Election Supervisory Authority is given to the Election Oversight Body (Bawaslu) and its subordinates in this case the Election Supervisory Body at the Regency / City level in Lampung Province. There is a strategic and significant Bawaslu function, which is to avoid potential election violations arising by implementing an optimal prevention strategy. Bawaslu has a strategic function and role in efforts to create democratic elections. This can also be seen in the Election of governors and deputy governors (pilgub) Lampung which took place on 27 June 2018. The problem in this paper is how the role of Bawaslu in the implementation of the governor election of Lampung Province in 2018 in an effort to realize democratic elections and what are the factors affect the performance of the Election Supervisory Body in the implementation of the election of governor of Lampung Province in 2018 in an effort to realize democratic elections?The results of the study are first, the role of the Election Supervisory Body in the implementation of the governor of Lampung province in 2018 in an effort to realize democratic elections contained in the voter data update based on population data and the determination of provisional voter candidates and permanent voter lists, the implementation of campaigns in the district / city, Election Logistics and Distribution, Implementation of Voting and Vote Counting of Election Results, Implementation of Election Socialization. Second, the factors that influence the performance of the Election Supervisory Body in the implementation of the election of the governor of Lampung Province in 2018 in an effort to realize a democratic election, namely structural factors, namely (1) Number of Personnel. (2) Supporting facilities. (3) The tasks and authority are not comparable to operational funds. Substance factors are regulatory issues, the government must also pay attention to the Fund, plus the amount of PPL that is not proportional to the area to be monitored, cultural factors namely the community chooses not based on conscience that is in accordance with the capacity and electability of the candidate for the Governor but based on the principle of regionalism. Keywords: Bawaslu, Election, Democratic